STRUCTURAL CONTEXTS AND COMMUNICATIVE CONNOTATIONS OF COORDINATORS IN THE ENGLISH USAGE OF SELECTED SECONDARY SCHOOL STUDENTS IN MAKURDI - Adaje, Ambrose Ochigbo; Oreoluwa, Beatrice Osaro (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
The study assesses the structural contexts and communicative connotations of conjunctive coordinators in the English usage of some secondary school students in Makurdi. The theoretical guide for the study is Error Analysis while the conceptual framework is structural grammar model description of coordinators in modern English usage. A proficiency test, tagged Use of Coordinators in English, was administered to sixty students, purposively sampled from two secondary schools. Using frequency and percentage statistics for data analysis, the results indicate lack of comprehension of structural usage contexts of semi-coordinators, quasi-coordinators and correlative coordinators. Also, there is lack of comprehension of the communicative connotations of all the coordinators in different sentential contexts. The study recommends that teachers should expose and drill students more on usage meanings and contexts of coordinators in English.